Animal prion diseases: the risks to human health - Houston, Fiona (Brain Pathol, 2019)
Transmissible spongiform encephalopathies (TSEs) or prion diseases of animals notably include scrapie in small ruminants, chronic wasting disease (CWD) in cervids and classical bovine spongiform encephalopathy (C‐BSE). As the transmission barrier phenomenon naturally limits the propagation of prions from one species to another, and the lack of epidemiological evidence for an association with human prion diseases, the zoonotic potential of these diseases was for a long time considered negligible. However, in 1996, C‐BSE was recognized as the cause of a new human prion disease, variant Creutzfeldt‐Jakob disease (vCJD), which triggered an unprecedented public health crisis in Europe. Large‐scale epidemio‐surveillance programs for scrapie and C‐BSE that were implemented in the EU after the BSE crisis revealed that the distribution and prevalence of prion diseases in the ruminant population had previously been underestimated. They also led to the recognition of new forms of TSEs (named atypical) in cattle and small ruminants and to the recent identification of CWD in Europe. At this stage, the characterization of the strain diversity and zoonotic abilities associated with animal prion diseases remains largely incomplete. However, transmission experiments in nonhuman primates and transgenic mice expressing human PrP clearly indicate that classical scrapie, and certain forms of atypical BSE (L‐BSE) or CWD may have the potential to infect humans. The remaining uncertainties about the origins and relationships between animal prion diseases emphasize the importance of the measures implemented to limit human exposure to these potentially zoonotic agents, and of continued surveillance for both animal and human prion diseases.